VIRTUAL OBSERVATORY AND COLITEC SOFTWARE: MODULES, FEATURES, METHODS - Pohorelov, A. V.; Khlamov, S. V.; Savanevych, V. E.; Briukhovetskyi, A. V.; Vlasenko, V. P. (Одеські астрономічні публікації, 2016)
In this article we described complex processing system created by the CoLiTec project. This system includes features, user-friendly tools for processing control, results reviewing, integration with online catalogs and a lot of different computational modules that are based on the developed methods. Some of them are described in the article. The main directions of the CoLiTec software development are the Virtual Observatory, software for automated asteroids and comets detection and software for brightness equalization. The CoLiTec software is widely used in a number of observatories in the CIS. It has been used in about 700 000 observations, during which 1560 asteroids, including 5 NEO, 21 Trojan asteroids of Jupiter, 1 Centaur and four comets were discovered.